Factors associated with not receiving HPV vaccine among adolescents by metropolitan statistical area status, United States, National Immunization Survey-Teen, 2016-2017 - Charnetta L. Williams; Tanja Y. Walker; Laurie D. Elam-Evans; David Yankey; Benjamin Fredua; Mona Saraiya; Shannon Stokley (Taylor & Francis Group, 2020)
The 2016 and 2017 National Immunization Surveys-Teen (NIS-Teen) highlighted disparities in human papillomavirus (HPV) vaccination coverage by metropolitan statistical area (MSA) status. Coverage with ≥1 dose of HPV vaccine was significantly lower among teens in suburban and mostly rural areas than it was among those in mostly urban areas. Reasons underlying this disparity are poorly understood; this analysis sought to identify sociodemographic factors associated with not initiating the HPV vaccine series and to determine whether these factors differed by MSA status. Using NIS-Teen data for a sample of 41,424 adolescents from the 2016 and 2017 survey years, multivariate logistic regression was utilized to assess associations between various sociodemographic factors and non-initiation of the HPV vaccine series by MSA status. Adjusted prevalence ratios and 95% confidence intervals are reported. A secondary analysis assessed missed opportunities for HPV vaccination by MSA status and estimated what coverage could be if these missed opportunities had not occurred. Most factors associated with not receiving HPV vaccine were similar across all three MSAs, including living in the South, having a mother with some college education, not having an 11-12-year-old well-child visit, and not receiving a provider recommendation for vaccination. Others were associated with non-initiation of the HPV vaccine series in only specific MSAs. Teens in suburban areas (82.2%) were more likely to miss opportunities for HPV vaccination than those in mostly urban (79.3%) areas. Coverage with ≥1 dose of HPV vaccine in all three MSAs would be substantially higher if these missed opportunities had been eliminated.